Trade - Growth Nexus in Nepal: A Gravity Model Approach - Kadel, Suren; Bhusal, Tara (The International Research Journal of Management Science, 2024)
Purpose of the Study: This study investigates the relationship between trade and economic growth in Nepal, focusing on how factors such as GDP, population, and geographical distance affect Nepal’s exports and imports. The research question addresses: "How do these factors influence Nepal's trade dynamics?" Methods/Design: A gravity model framework was used, with panel data analysis employing fixed and random effects models. The Hausman test determined the appropriate model. Data on trade partners' GDP, population, and geographical distance were collected to estimate the model. Findings: The analysis shows that Nepal’s exports are positively influenced by the GDP and population of trade partners, while geographical distance negatively impacts trade. Closer countries are more favorable trading partners. The random effects model proved to be the most appropriate estimator, with both the export and import models demonstrating strong explanatory power. Conclusion/Implications: The findings suggest that Nepal should focus on export diversification and strengthen regional trade relations to foster economic growth. Policymakers can use these insights to improve trade strategies and regional cooperation. Limitations of the Study: The study is limited by data constraints and does not account for informal trade flows, which could affect the results. Originality of the Study: This study uniquely applies the gravity model to Nepal’s trade context, addressing challenges faced by landlocked developing countries.